2018
DOI: 10.29298/rmcf.v6i28.257
|View full text |Cite
|
Sign up to set email alerts
|

Características anatómicas, físico-mecánicas y de maquinado de la madera de mezquite (Prosopis velutina Wooton)

Abstract: Las características anatómicas, físico-mecánicas y de maquinado de la madera de mezquite (Prosopis velutina) fueron determinadas. Se recolectaron en el estado de Sonora cinco trozas de dos metros a partir del tocón. El estudio anatómico se efectuó conforme a lo estipulado por la IAWA. Las propiedades físico-mecánicas se evaluaron de acuerdo a las normas DIN. El maquinado se efectuó de forma manual y para la evaluación de la superficie se tomó como base la norma ASTM D 1666-87. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Cell wall thickness averaged 3,91 µm, showing no significant differences among the three sections. Beeckman (2016) mentions that the environment influences both the growth and quality of the anatomical elements of wood, whereas Rodríguez et al (2015) point out that the treatment conducted to separate the anatomical elements will have an influence on fibre measurement results.…”
Section: Measurement Of Anatomical Elements Of Interest Guazuma Crini...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall thickness averaged 3,91 µm, showing no significant differences among the three sections. Beeckman (2016) mentions that the environment influences both the growth and quality of the anatomical elements of wood, whereas Rodríguez et al (2015) point out that the treatment conducted to separate the anatomical elements will have an influence on fibre measurement results.…”
Section: Measurement Of Anatomical Elements Of Interest Guazuma Crini...mentioning
confidence: 99%
“…Among the species used for plantation purposes, bolaina blanca (Guazuma crinita Lam.) stands out (Miguel et al 2019, Rodríguez et al 2015. This forest species is widely cultivated in the country owing to its advantage of being a fast-growing species harvestable at an early age as well as the large demand for its wood for construction, furniture and mouldings (Revilla 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the specialization and selection in host use arose from a costbenefit balance of physical and/or nutritional factors (Saint-Germain et al, 2007a). Physical characteristics of the wood, such as its density, volume, and decomposition rate depend on the quantity and type of cellular elements that constitute it (Navarro-Martínez et al, 2005) and vary according to species, the zone, and climatic conditions where the trees grow (Rodríguez-Anda et al, 2015). For example, in temperate forests, a higher abundance of cerambycids has been found in wood with low density (0.2-0.5 g/cm 3 ) (Saint-Germain et al, 2007a, 2007b, and in TRF, more cerambycids emerged from wood with low density too (0.4-0.46 g/cm 3 ) (Lanuza-Garay & Barrios, 2018).…”
Section: Introductionmentioning
confidence: 99%